Comparison of Buccal Midazolam with Rectal diazepam in Status Epilepticus in Terms of Recurrence of Seizures and Risk for Treatment Failure - Tariq Saeed ,Muhammad Zahoor Ul Haq,Nazish Masood Kiani (Journal of Rawalpindi Medical College, 2015)
Background: To compare buccal midazolam with rectal diazepam in status epilepticus in terms of recurrence of seizures and risk for treatment failure Methods: In this randomized controlled study a total of 410 children with status epilepticus irrespective of cause were included. Patients were randomly divided into two groups. Patients in group A (n=205) were treated with buccal midazolam 0.3 mg/kg/dose and patients in group B (n=205) were treated with rectal diazepam 0.3 mg/kg/dose. Both groups were observed for duration of controlling of seizures within 10 minutes to see the risk for treatment failure and to check for recurrence of seizure within one hour after initial control of seizure. Results: The average age of the patients was 4.66±2.95 years. Mean age was not significant between groups while mean duration of control of seizure was significant between groups. Recurrence was significantly high in group B as compared to group A. Group A was more effective than group B because the recurrence rate was low and treatment was significantly effective (p=0.002). Conclusion: - Buccal midazolam offers a promising alternative to rectal diazepam for the treatment of seizures in children.